When should CT urography be used as the initial imaging test in adults with gross hematuria?. Issue 8 (August 2016) - Kern, Thomas; Remtulla, Fariz; Singh, Jasminder; Wen, Frances; Sanders, Karen
Abstract : Evidence‐Based Answer : Computed tomography urography (CTU) is appropriate as an initial imaging test to evaluate gross hematuria in adults older than 40 years or adults younger than 40 years with predisposing medical conditions for urologic disease. Unenhanced CT is appropriate for adults 40 years or younger without predisposing medical conditions for urologic disease. In patients with gross hematuria, CTU has a positive likelihood ratio (LR+) of 108 and a negative likelihood ratio (LR‐) of 0.07 for detecting bladder cancer. Patients with gross hematuria are twice as likely as those with microscopic hematuria to have an abnormal CTU (SOR: C, cohort studies of disease‐oriented evidence and consensus guidelines).